2020
DOI: 10.1016/j.thromres.2020.07.047
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer level is associated with the severity of COVID-19

Abstract: Introduction Abnormal coagulation function has been demonstrated to be involved in the disease progression of COVID-19. However, the association between D-dimer levels and the severity of COVID-19 is not clear. The study was aimed to investigate the association between D-dimer levels and the severity of COVID-19 based on a cohort study and meta-analysis. Materials and methods Demographic and clinical data of all confirmed cases with COVID-19 on admission to Tongji Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
1
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(181 citation statements)
references
References 24 publications
(41 reference statements)
5
140
1
20
Order By: Relevance
“…Ang II is also related to the activation of thrombogenic factors. This may explain the elevation of D-dimer levels, which are monitored in COVID-19 patients, particularly in those with severe infection 69 , 70 . Consequently, the activation of a procoagulant state may induce a hemorrhagic stroke 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Ang II is also related to the activation of thrombogenic factors. This may explain the elevation of D-dimer levels, which are monitored in COVID-19 patients, particularly in those with severe infection 69 , 70 . Consequently, the activation of a procoagulant state may induce a hemorrhagic stroke 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated D‐dimer is common in COVID‐19 patients and may be attributed to sepsis‐induced coagulopathy and reflect the higher thromboembolic risk in severe COVID‐19 cases 26,188 . D‐dimer levels were significantly higher in severe than in nonsevere COVID‐19 patients, 42 and higher in patients with PE than those without PE 26 ; and D‐dimer > 0.5 mg/L is associated with severe disease of COVID‐19 30 . A meta‐analysis including 5872 COVID‐19 patients also found higher D‐dimer concentrations were associated with severity and mortality in these patients 189 .…”
Section: Laboratory Indicatorsmentioning
confidence: 98%
“…A good understanding of the possible risk factors in combination to disease immunopathology associated with COVID‐19 severity is helpful for clinicians in identifying patients who are at high risk and require prioritized treatment to prevent disease progression and adverse outcome 4 . Risk factors range from demographic factors, such as age, 3,5–7 sex and ethnicity, 8,9 diet and lifestyle habits 10,11 to underlying diseases 12–22 and complications, 23–26 and laboratory indications 27–39 . Many studies have reported predictive models using various risk factors to identify high‐risk patients that may develop severe and critical illness 40 .…”
Section: Introductionmentioning
confidence: 99%
“…[164][165][166][167][168][169] Raised D-Dimer levels were frequently reported among severe COVID-19 patients, correlated with poor prognosis and high mortality. [169][170][171] Moreover, it has been observed among COVID-19 that prothrombin time (PT) and activated partial thromboplastin time (aPTT) often increases, fibrin degradation products increase, with severe thrombocytopenia leading to fatal disseminated intravascular coagulation (DIC), which demands relentless alertness, observance, and quick intervention. 169,172 It has been reported that CP contains neutralizing antibodies, anti-inflammatory cytokines, clotting factors, natural antibodies, defensins, pentraxins, and other proteins obtained from recovered donors.…”
Section: Effects Of Convalescent Plasma On the Coagulopathy Of Covid-19mentioning
confidence: 99%